O impacto do início do tratamento em portadores do vírus da hepatite C: uma leitura lacaniana - Tiferes, Sandra Rozenblit (2010)
The diagnosis of a chronic illness affects all spheres of a person's life, causing physical, social, family and professionals changes. In chronic infectious diseases of viral origin, current protocols and consensus towards treatment for infected individuals focus on fighting the virus and usually do not cover these situations, what makes it more difficult for the patient to withstand the treatment. In most cases, hepatitis C is not discovered by physical symptoms, but by blood donation or routine laboratorial tests. So there is a great impact when receiving this diagnosis, that seems to be repeated when the drug treatment is prescribed, and this can occur years after receiving the diagnosis. In this study, based on Lacanian psychoanalysis, a qualitative research has been carried out with the overall objective of providing a space for listening in order to: provide the emergence of a demand for psychoanalytical treatment, as when speaking, people who are infected can be aware of their stories, their signifying chain, fears, fantasies and anxieties, and therefore become less alienated and more active in the process they are experiencing; to understand the impact of the diagnosis for the person infected by the virus until the start of treatment with drugs; to demonstrate the possibility of contributions from a psychoanalyst in hospitals and wards. Five patients were followed up during a half year, before starting the treatment at the Clinic of Infectious Diseases of UNIFESP (Federal University of São Paulo). Semi-structured interviewing was used as an instrument for the first meeting to establish a transference relationship and provide the participants with an opportunity to familiarize with the proposed setting. In subsequent meetings it was used free association, main method of psychoanalysis. As a result it could be seen that for each individual, the diagnosis raises an unique matter that is connected to his life story, to his own chain of signifiers linked to primal repression, Law as interdiction, and the desire to establish himself as the desire of the Other. For Laura, the diagnosis recalls sexual abuse, aggression and death issues. For Mario the diagnosis brings back the matter of how to be a man that can please a woman, which has led him to drugs and consequently to the infection. Therefore, providing a space for listening allowed individual issues to surface and through analytical intervention it was possible to promote the involvement of each of the individuals with their own symptoms and treatment